The Use of Prohibited Substances by Athlete are Covered in Doping Offenses - Gunawan, Candra; Muchtar, Andhyka; Nasir, Muh. (Journal of Legal and Cultural Analytics, 2023)
Doping is the administration of oral or paralytic drugs or concoctions to an athlete with the aim of increasing unnatural accuracy. In Indonesia, the prohibition on the use of doping consisting of prohibited substances and/or methods is regulated in Law Number 11 of 2022 concerning Sports. The use of doping is contrary to the principle of "fair play" in matches and also harms the spirit of sport which upholds the values of honesty and justice. However, currently the law on sports in Indonesia does not yet contain criminal sanctions regarding violations of the use of prohibited substances and/or methods, so it is still based on the Law on Narcotics in imposing sanctions. A normative method based on legal materials as the main source.